Implementation of Information Technology Governance in Man 1 Medan Using the Cobit 5 Framework - Harahap, Aninda Muliani; Ikhwan, Ali (Politeknik Ganesha Medan, 2023)
In response to the rising usage of information technology, organizations should implement an information technology plan aligned with company goals. Similarly, in education, information technology is used for business purposes. The purpose of this research is to look into the implementation of information technology governance utilizing the COBIT 5 framework. This study was carried out at MAN 1 MEDAN. The survey technique collects data through the distribution of questionnaires to information technology managers and key users in various businesses. Descriptive research discovered that the state of governance and information technology implementation at MAN 1 MEDAN was at level 3 on a scale of 0 to 5. This demonstrated that institutional behaviors had been adequately recorded and internalized. This study aims to contribute to research on the use of information technology governance, particularly for educational institutions and information technology managers, as input material in the management of information technology resources in other institutions. These associated problems are essential considerations for parents or students when selecting a Medan MAN 1 school with a high degree of IT facilities.